Telomere Dysfunction in Chronic Lymphocytic Leukemia - Jebaraj, Billy Michael Chelliah; Stilgenbauer, Stephan (Frontiers in Oncology, 2021)
Telomeres are nucleprotein structures that cap the chromosomal ends, conferring genomic stability. Alterations in telomere maintenance and function are associated with tumorigenesis. In chronic lymphocytic leukemia (CLL), telomere length is an independent prognostic factor and short telomeres are associated with adverse outcome. Though telomere length associations have been suggested to be only a passive reflection of the cell’s replication history, here, based on published findings, we suggest a more dynamic role of telomere dysfunction in shaping the disease course. Different members of the shelterin complex, which form the telomere structure have deregulated expression and POT1 is recurrently mutated in about 3.5% of CLL. In addition, cases with short telomeres have higher telomerase (TERT) expression and activity. TERT activation and shelterin deregulation thus may be pivotal in maintaining the minimal telomere length necessary to sustain survival and proliferation of CLL cells. On the other hand, activation of DNA damage response and repair signaling at dysfunctional telomeres coupled with checkpoint deregulation, leads to terminal fusions and genomic complexity. In summary, multiple components of the telomere system are affected and they play an important role in CLL pathogenesis, progression and clonal evolution. However, processes leading to shelterin deregulation as well as cell intrinsic and microenvironmental factors underlying TERT activation are poorly understood. The present review comprehensively summarizes the complex interplay of telomere dysfunction in CLL and underline the mechanisms that are yet to be deciphered.